Ecological Citizenship Through Indigenous Forest Governance: Operationalizing Tena Troikha Principles - Fadli Marthen Sutrisno; Agustinus Kespo (Lentera Negeri, 2026)
Tena Troikha, a sacred forest of the Ormu Indigenous community in Nechebei, Papua, is proposed as a culturally grounded mechanism for forest protection. Indigenous ecological knowledge and customary institutions may contribute to local conservation, yet empirical evidence for their effectiveness and operational mechanisms remains limited. This study employed an ethnographic case study design conducted from October 2025 to March 2026, combining field observation, in-depth interviews with customary leaders 10, members of the Ormu Indigenous community 50, village officials 5, local stakeholders 5, relevant government representatives 5, and documentation review. Participants were selected using purposive and snowball sampling to ensure representation of key knowledge holders. Data were analyzed through iterative thematic coding, with triangulation across participant narratives, field notes, and documentary sources to strengthen credibility. Descriptive findings indicate that Tena Troikha is maintained through customary prohibitions, spiritual authority, and collective responsibility. Forest areas under Tena Troikha showed limited visible disturbance during field visits, and participants consistently linked ecological preservation to ancestral norms. Interpretively, these mechanisms support locally legitimate forest protection, though the study did not quantify deforestation rates or compare sacred versus non-sacred areas. Findings emphasize the role of Indigenous institutions and ecological knowledge in regulating sustainable resource use. Tena Troikha illustrates how Indigenous governance can contribute to forest conservation within culturally specific contexts. While findings are not statistically generalizable beyond the Ormu community, they highlight the potential of integrating customary authority, spiritual values, and participatory management into collaborative conservation strategies. Future research should combine qualitative insights with quantitative forest-cover monitoring to evaluate measurable ecological outcomes.